2022
DOI: 10.1097/ruq.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Liver Ultrasound Attenuation

Abstract: ObjectivesNonalcoholic fatty liver disease (NAFLD) is the most widespread chronic liver disease type in the Western countries. Ultrasound (US) is used for NAFLD and hepatic steatosis (HS) grading. The most popular US method for NAFLD assessment is the hepatorenal index (HRI), but because of its limitations, other noninvasive methods have been developed. The Resona 7 US system has recently incorporated an US attenuation–related quantitative feature, liver ultrasound attenuation (LiSA), for HS estimation. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Two complementary lines of evidence support this assumption. First, lipid accumulation in other organs (e.g., hepatic steatosis) is now recognized to cause a very similar sonographic pattern 23 . Second, Fornander et al 8 using quantitative muscle MRI have shown recently that cDMD had increased fat fractions in the thigh and calf muscles relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Two complementary lines of evidence support this assumption. First, lipid accumulation in other organs (e.g., hepatic steatosis) is now recognized to cause a very similar sonographic pattern 23 . Second, Fornander et al 8 using quantitative muscle MRI have shown recently that cDMD had increased fat fractions in the thigh and calf muscles relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been a significant effort in investigating and developing non-invasive alternatives for steatosis evaluation, specifically in MRI and ultrasound. Several studies have shown the potential of ultrasound attenuation index to detect hepatic steatosis [9][10][11]. Using a clinically approved linear probe, the same technique has yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%